Genetic aspects of admissions to a paediatric intensive care unit. Issue 5 (May 1991) - FitzPatrick, D R; Skeoch, C H; Tolmie, J L
Abstract : Of 821 consecutive admissions to a paediatric intensive care unit, 47 (5.7%) were for chromosomal or monogenic disorders. These patients had more readmissions, longer mean stays, and a higher mortality rate than the group as a whole. In two of the four cases that died of single gene disorders, failure to store DNA made genetic counseling difficult.